Medication use in Poland for children and adolescents with neurodevelopmental disorders: before, during and after the COVID-19 pandemic - a retrospective pharmacoepidemiological study using national reimbursement data - Silczuk, Andrzej; Hołownia-Voloskova, Malwina; Mosiołek, Anna; Roubinek, Otton; Bliźniewska-Kowalska, Katarzyna; Zakrzewski, Krzysztof Marcin; Czech, Marcin (Frontiers in Pharmacology, 2026)
BackgroundThe pandemic profoundly disrupted healthcare and education systems, potentially affecting the pharmacological management of neurodevelopmental disorders (NDDs) in children and adolescents.ObjectiveTo examine national trends in psychotropic drug dispensing among pediatric patients with NDDs in Poland before, during, and after the COVID-19 pandemic.MethodsA retrospective pharmacoepidemiological analysis was conducted using data from the IQVIA Pharmascope database, which records all reimbursed medicines dispensed by community pharmacies in Poland. Monthly and annual dispensing volumes were analyzed for January 2018–December 2024, focusing on drugs commonly used in ADHD, autism spectrum disorder, and intellectual disability. Three time periods were compared: pre-pandemic (2018–February 2020), pandemic (March 2020–June 2022), and post-pandemic (July 2022–December 2024).ResultsA marked surge in psychotropic drug dispensing was observed in 2021, with total annual utilization jumping to nearly 2.7 billion dispensed days of therapy (DOT)—more than double the levels seen in any prior year. This represents a 161% increase compared with 2020, when volumes were approximately 1.0 billion DOT. The most substantial increases occurred for sedative and anxiolytic agents (hydroxyzine, diazepam, alprazolam, lorazepam) and antipsychotics (olanzapine, aripiprazole, risperidone, chlorprothixene, haloperidol, levomepromazine), consistent with pandemic related stress, limited access to non-pharmacological care, and possible stockpiling. Dispensing volumes fell sharply in 2022 to around 1.1 billion DOT, returning close to pre-pandemic levels and suggesting these effects were transient. A modest upward trend resumed thereafter, with volumes rising to approximately 1.2 billion DOT in 2023 and 1.5 billion DOT in 2024, indicating gradual recovery but remaining far below the extraordinary 2021 peak.ConclusionThe COVID-19 pandemic induced broad but temporary increases in pediatric psychotropic drug dispensing, except for ADHD pharmacotherapies, which demonstrated a persistent upward trend. These findings suggest lasting shifts in diagnostic and therapeutic practices and underscore the need for continued monitoring of stimulant use and prescribing appropriateness in pediatric neurodevelopmental care.